Soil fertility and productive indicators of Cenchrus purpureus (Schumach) Morrone cv. Cuba CT-115 in a biomass bank - G. Crespo (Revista Cubana de Ciencia Agrícola, 2017)
The effect of Cenchrus purpureus cv. Cuba CT-115 biomass bank technology with ten years of exploitation on the soil fertility and some morphological indicators of this grass was researched. The study was carried out in a filling grayish brown soil, in the dairy unit number 11, belonging to El Abra farm, from El Tablón enterprise, in Cienfuegos. It was found an increase of the OM content (3.19 to 3.55 %, P <0.0094) and a decrease of the assimilable P (24.30 to 18.88 ppm, P <0.0089). Although the physical indicators did not show significant variations, the apparent density showed slight numerical increase. In this scenario, the macrofauna biomass (including the number of worms) and root weight was higher (P <0.001) in the most superficial depth (0- 15 cm), while the indicators tillers bunches -1 , dry matter yield, stem thickness and length of the fourth leaf showed adequate values and with little variation in the dry season 2013 and 2014. It is concluded that the soil that occupied the biomass bank had an increase of the OM content and a decrease of the assimilable P after ten years of exploitation. In this area, acceptable values were also found in grass indicators, the macrofauna activity (especially worms) and root biomass, although the CT-115 plants showed low nutritive value.